Leber's hereditary optic neuropathy (LHON)-associated ND5 12338T > C mutation altered the assembly and function of complex I, apoptosis and mitophagy. (22nd March 2018) - Zhang, Juanjuan; Ji, Yanchun; Lu, Yuanyuan; Fu, Runing; Xu, Man; Liu, Xiaoling; Guan, Min-Xin
Abstract: Mutations in mitochondrial DNA (mtDNA) have been associated with Leber's hereditary optic neuropathy (LHON) and their pathophysiology remains poorly understood. In this study, we demonstrated that a missense mutation (m.12338T>C, p.1M>T) in the ND5 gene contributed to the pathogenesis of LHON. The m.12338T>C mutation affected the first methionine (Met1) with a threonine and shortened two amino acids of ND5. We therefore hypothesized that the mutated ND5 perturbed the structure and function of complex I. Using the cybrid cell models, generated by fusing mtDNA-less (ρ°) cells with enucleated cells from LHON patients carrying the m.12338T>C mutation and a control subject belonging to the same mtDNA haplogroup, we demonstrated that the m.12338T>C mutation caused the reduction of ND5 polypeptide, perturbed assemble and activity of complex I. Furthermore, the m.12338T>C mutation caused respiratory deficiency, diminished mitochondrial adenosine triphosphate levels and membrane potential and increased the production of reactive oxygen species. The m.12338T>C mutation promoted apoptosis, evidenced by elevated release of cytochrome c into cytosol and increased levels of apoptosis-activated proteins: caspases 9, 3, 7 and Poly ADP ribose polymerase in the cybrids carrying the m.12338T>C mutation, as compared with control cybrids. Moreover, we also document the involvement of m.12338T>C mutation in decreased mitophagy, as showed by reduced levels of autophagy protein light chain 3 and accumulation of autophagic substrate p62 in the in mutant cybrids as compared with control cybrids. These data demonstrated the direct link between mitochondrial dysfunction caused by complex I mutation and apoptosis or mitophagy. Our findings may provide new insights into the pathophysiology of LHON.